2014
DOI: 10.4103/2229-516x.140733
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of insulin resistance by various methods with fasting insulin in obese

Abstract: Background:Several studies indicate that obesity is closely related to insulin resistance (IR). However, this relationship has not been adequately explored.Aims:This study aims to evaluate the prevalence of IR among obese using some indirect methods for assessment of IR.Materials and Methods:We analyzed the correlation of fasting insulin (FI) with body mass index. We examined 100 obese and overweight. Anthropometric measurements were done for all individuals. Blood lipids parameters, glucose, and insulin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the present study, insulin resistance was seen in about 75%–80% of obese PCOS women and in about 18%–20% of nonobese PCOS women, based on fasting insulin cutoff value of ≥12.2 μU/mL,[1819] HOMA-IR of ≥2.5,[18202122] and QUICKI index of <0.33[182122] for determining insulin resistance. Fasting insulin and QUICKI values were statistically significantly higher ( P < 0.05) in both groups of PCOS women (obese and nonobese) when compared with their age- and BMI-matched controls.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the present study, insulin resistance was seen in about 75%–80% of obese PCOS women and in about 18%–20% of nonobese PCOS women, based on fasting insulin cutoff value of ≥12.2 μU/mL,[1819] HOMA-IR of ≥2.5,[18202122] and QUICKI index of <0.33[182122] for determining insulin resistance. Fasting insulin and QUICKI values were statistically significantly higher ( P < 0.05) in both groups of PCOS women (obese and nonobese) when compared with their age- and BMI-matched controls.…”
Section: Discussionmentioning
confidence: 76%
“…All women also underwent biochemical tests (prolactin, thyroid-stimulating hormone, 17-hydroxyprogesterone, and post 1-mg dexamethasone serum cortisol) for the exclusion of secondary causes of PCOS. Various insulin resistance indices[1819202122] were used for assessing insulin resistance namely fasting insulin level (cutoff value; ≥12.2 μU/ml), Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) (cutoff value; ≥2.5), and Quantitative Insulin Sensitivity Check Index (QUICKI) (cutoff value; <0.33). Whole-body dual-energy X-ray absorptiometry (DXA) scan using Hologic DXA QDR 4500 Discovery A machine with a coefficient of variation (CV) of 2% was used for the study of body composition and estimation of VAT in all women (both cases and controls).…”
Section: Methodsmentioning
confidence: 99%
“…Our study revealed the strong positive correlation between HOMA-IR and fasting insulin levels in study participants. A study that evaluated the correlation of insulin resistance assessed by different indices such as McAuley, HOMA and QUICKI, came to a conclusion that fasting insulin is sensitive and could be used as a simple test for the detection of insulin resistance in obese individuals [ 50 ]. Thus, it could be concluded that obese insulin-resistant individuals show significantly worse metabolic profile compared to non-insulin resistant ones.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improvements in blood glucose uptake ( Figure 2 ), our result showed that CmNo1 treatment also decreased fasting serum insulin levels in HFD-fed mice ( Figure 4 ), indicating insulin utilization by tissues. Fasting insulin measurement has been considered as the most practical and accurate approach for insulin sensitivity [ 53 , 54 ]. Hence, the results inferred that improvement in blood glucose levels could be due to the positive effect of CmNo1 treatment on insulin receptor sensitivity, providing a new therapeutic avenue for type 2 DM.…”
Section: Discussionmentioning
confidence: 99%